Grocery product arrangement using cluster analysis - Seva, Rosemary R. (Animo Repository, 2019)
Literature on grocery layout improvements are limited. Grocery owners do not consider customer expectations in layout design. This study aims to determine products that must be grouped together in a grocery store based on customer's expected adjacency. The main method used is card sorting to identify customers' mental model on product arrangement. A representative grocery store was used to test the proposed method. There were 39 products used in the card sorting experiments based on the movable contents of the selected grocery store. Forty participants participated in an open card sorting to determine clustering of products. After groups had been determined, suitable names were identified for the groups. Pairwise Exchange Method (PEM) was then used within each group to determine how to arrange products within a certain area. Results of the study showed that customers expect products to be grouped according to use. Complementary and substitute products should also be placed close to each other. © 2019 Turkiye Klinikleri Journal of Medical Sciences. All rights reserved.